2017
DOI: 10.1080/1068316x.2017.1324027
|View full text |Cite
|
Sign up to set email alerts
|

Treatment effectiveness for offenders with autism spectrum conditions: a systematic review

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 68 publications
1
18
0
Order By: Relevance
“…Both published evaluations (Phase 1) and survey responses (Phase 2) regarding individuals with Intellectual and Developmental Disabilities (IDD) were excluded from the current study as the presence of an IDD is considered to be an additional responsivity factor that needs to be accounted for in treatment programs. Consequently, interventions for individuals with IDD are often 'adapted' to meet the literacy, social and cognitive needs of this group to ensure their accessibility (Melvin, Langdon, & Murphy, 2017;Keeling & Rose, 2006;Williams, Wakeling, & Webster, 2007). As a result, this group are often examined separately to those who do not have an IDD.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Both published evaluations (Phase 1) and survey responses (Phase 2) regarding individuals with Intellectual and Developmental Disabilities (IDD) were excluded from the current study as the presence of an IDD is considered to be an additional responsivity factor that needs to be accounted for in treatment programs. Consequently, interventions for individuals with IDD are often 'adapted' to meet the literacy, social and cognitive needs of this group to ensure their accessibility (Melvin, Langdon, & Murphy, 2017;Keeling & Rose, 2006;Williams, Wakeling, & Webster, 2007). As a result, this group are often examined separately to those who do not have an IDD.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…It is important to emphasise in any discussion of ASD and offending that individuals with ASD are not more likely to carry out offending behaviours compared to the general population (e.g., Mouridsen et al, 2008). However, research has indicated some of the ASD symptomology which can contribute to a variety of offending behaviour (e.g., Baron-Cohen, 1988;Everall & Lecouteur, 1990;Chesterman & Rutter, 1993;Siponmaa et al, 2001;Barry-Walsh & Mullen, 2004;Schwartz-Watts, 2005;Mouridsen et al, 2008;Ledingham & Mills, 2015;Allely & Creaby-Attwood, 2016;Lazaratou, Giannopoulou, Anomitri, & Douzenis, 2016;Melvin, Langdon, & Murphy, 2017;Allely & Faccini, 2018;Allely, 2019). For example, there is a growing number of studies which have explored the core features of ASD which may contribute to inappropriate sexual behaviours.…”
Section: Asd and Sexual Offendingmentioning
confidence: 99%
“…Although research suggests that individuals with an ASD in non-forensic contexts benefit from adapted psychological therapies such as social skills interventions, cognitive behaviour therapy and mindfulness (Gaus, 2007;Spain, O'Neil, Harwood, & Chaplin, 2016), there remains a lack of detailed research into psychological and non-psychological therapies for offenders with an ASD (Melvin Langdon, & Murphy, 2017). As Spain and colleagues (2016) also highlights in a review of non-forensic psychological interventions, there is a need to examine how therapeutic outcomes are assessed with individuals who have an ASD including what formal measures are employed and when, as well as using appropriate comparative data.…”
Section: Engagement With Psychological Interventions and Role Of Stafmentioning
confidence: 99%